Macroalgal treatment to alleviate the strawberry yield loss caused by Macrophomina phaseolina (Tassi) Goid. in greenhouse cultivation system - Tajdinian, Samaneh; Rahmati-Joneidabad, Mostafa; Ghodoum Parizipour, Mohamad Hamed (Frontiers in Sustainable Food Systems, 2022)
The application of algae has been considered a key element for integrated disease management in sustainable agriculture. These organisms can act as a bio-stimulant for induction of resistance against a variety of abiotic and biotic agents that cause economical loss to crop production globally. Charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. is one of the biotic agents restricting strawberry (Fragaria × ananassa Duch.) yield in many cultivation sites. Herein, the foliar application of brown alga (Sargassum angustifolium) was investigated for the reduction of the disease symptoms and improvement of vegetative and reproductive indices in strawberries under greenhouse conditions. The results showed that alga-treated infected plants showed symptom remission. Moreover, vegetative and reproductive indices of alga-treated plants were significantly improved. Biochemical analysis showed that in alga-treated infected plants the total phenol, flavonoids, and total antioxidant activity were significantly increased compared to non-treated infected plants. Furthermore, the content of defense-related enzymes, viz. phenylalanine ammonia-lyase and polyphenol oxidase, were significantly increased in the infected plants pre-treated with the alga extract. Foliar application of S. angustifolium extract can induce defense responses in strawberry plants infected by M. phaseolina leading to improved growth indices of the plants. It can be concluded that S. angustifolium extract is a promising source of bio-stimulants for induction of disease resistance against charcoal rot disease in strawberry cultivations.